2023
DOI: 10.1039/d2dd00100d
|View full text |Cite
|
Sign up to set email alerts
|

A fully automated platform for photoinitiated RAFT polymerization

Abstract: Oxygen tolerant polymerizations including Photoinduced Electron/Energy Transfer-Reversible Addition-Fragmentation Chain-Transfer (PET-RAFT) polymerization allow for high-throughput synthesis of diverse polymer architectures on the benchtop in parallel. Recent developments have further increased throughput...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A key requirement for this combinatorial approach is improved oxygen tolerance during polymerization. , Recently, high-throughput synthesis of well-defined high molecular weight polymers via enzymatically degassed RAFT polymerization in a 96-well plate was reported . There are also several examples of performing PET-RAFT in a high-throughput manner, but similar ATRP systems are still rare …”
Section: Introductionmentioning
confidence: 99%
“…A key requirement for this combinatorial approach is improved oxygen tolerance during polymerization. , Recently, high-throughput synthesis of well-defined high molecular weight polymers via enzymatically degassed RAFT polymerization in a 96-well plate was reported . There are also several examples of performing PET-RAFT in a high-throughput manner, but similar ATRP systems are still rare …”
Section: Introductionmentioning
confidence: 99%
“…This results in the following expression (10) At monomer concentration c = c**, the number of monomers per correlation blob becomes comparable to the number of monomers per chain Kuhn length g(c**) = b/l. Rewriting this condition in terms of B th , we have (11) In the monomer concentration range such that c > c**, chain sections within the correlation length are rod-like, which is reflected in the concentration dependence of g = (cl 3 ) −0.5 (Figure 1b).…”
Section: Solutionsmentioning
confidence: 99%
“…Although justifiable from an academic and fundamental point of view, it would be highly beneficial to expand the cargo scope and evaluate if PISA can not only serve as an alternative, but also enabling technology for certain cargos. These larger scale screening studies on typically expensive cargos could be facilitated by recently reported oxygen‐tolerant RAFT systems enabling polymerizations in μL volumes, 122,156 simulation studies to minimize the tedious optimization processes typically involved in multi‐parametric PISA systems 169–172 and fully automated RAFT platforms 252 Benchmarking against other DDS.…”
Section: Challenges Toward In Vivo Studies and Clinical Translationmentioning
confidence: 99%